Analysis of verbal and non verbal signs in global warming advertisements created by redbubble - Hostiani, Kadek Lilis; Sulatra, I Komang; Nugraha, Gusti Bagus Wahyu (Journal of Language and Applied Linguistics, 2022)
Global warming advertisements are used to invite people to save the earth by reducing the use of plastic, planting trees, etc. that may cause global warming. Verbal and nonverbal communication tools that are used by humans to interact, whether through messages, sounds, pictures, and gestures. This study aims to find out the verbal and non-verbal signs used in global warming advertisements and to analyze the meaning of those signs. The data were taken from the redbubble website on Pinterest. The data were collected by observation method. The analysis was done by the descriptive qualitative method. The study started by analyzing the verbal and non-verbal signs which are based on the theory of semiotics by Saussure (1893). Then, the analysis of the meaning of the verbal and non-verbal signs was done by using the theory of meaning proposed by Barthes (1977). In addition, the study of colors was done using the approach of color term submitted by Wierzbicka (1996). The result of the research shows that global warming advertisements invite and persuade people to avoid the action that will damage nature or the environment and from the advertisement we can find verbal and non-verbal signs and the meaning of an advertisement.